Effect of microbial consortia on total carbon, C:N ratio and enzymatic activity during rice-wheat straw decomposition under incubation study - RANI, CHANDNI; SINGH, MAHENDRA; CHATTOPADHYAYA, NILANJAN; KUMAR, SANTOSH; KOHLI, ANSHUMAN; ARORA, SANJAY (Journal of Soil and Water Conservation, 2025)
In Northern and Indo Gangetic Plains of India, in-situ burning of rice and wheat crops residues is practiced by majority of farmers’ which deteriorates soil health and environmental quality by liberating mostly carbon dioxide and leaving ash in at the surface of soil. Bacteria and fungi have the potential for lignocelluloses degradation and can be used for the in-situ decomposition of crop residues. An experiment was conducted with the consortia having fungi and bacteria for the study of crop residue decomposition with the treatments viz., T1- Control (Rice straw)+ soil; T2- Rice straw+ Consortium+ soil; T3- Rice straw+ Pusa decomposer+ soil; T4- Wheat straw+ Consortium+ soil; T5- Wheat straw+ Pusa decomposer+ soil. The experimental results revealed that the evolution of gaseous ammonia and carbon dioxide was found increased with the subsequent intervals, the highest value of 448.97 mg/kg straw and 69.65 mg CO2-C/g was found under the treatment of T5 (Wheat straw+ Pusa decomposer). However, the C: N ratio was found to be lowest (35.89) in treatment T5 (Wheat straw+ Pusa decomposer). The highest activity was observed of treatment T5 (54.73 μg TPF/g/hr) followed by T4>T3>T2>T1, respectively and maximum at 75th DAI (47.10 μg TPF/g/hr). The interaction was found to be highest at 75th DAI (56.92 μg TPF/g/hr) with T5 Wheat straw+ Pusa decomposer+ soil which was at par with 60th DAI (56.63 μg TPF/g/hr) of T5. It may be concluded from the investigated findings that the application of microbial consortia having bacteria and fungi is capable to decompose the rice residue quickly and also increase the enzymatic activity in the substrate.